Preschool teachers’ emotional competence and teacher self-efficacy towards preschool performance in Zhejiang Province of China - Ye, Xiaolu; Ahmad, Nor Aniza; Burhanuddin, Nur Aimi Nasuha; Na, Meng; Li, Danwei (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This study investigates the interplay between emotional competence, self-efficacy, and teaching experience in determining preschool teachers’ performance. Drawing on Bandura’s Theory of Self-Efficacy, Goleman’s Emotional Intelligence Theory, and Bronfenbrenner’s Ecological Systems Theory, the research employs a quantitative approach, analyzing responses from preschool teachers in Zhejiang province, China. Key findings reveal that emotional competence significantly predicts teachers’ performance and self-efficacy, with self-efficacy further mediating this relationship. Interestingly, while teaching experience moderates the impact of emotional competence on self-efficacy, it does not significantly influence the relationship between self-efficacy and teaching performance. The study underscores the critical role of emotional competence in teaching efficacy and highlights the complexity of how teaching experience interacts with these dynamics. These insights are crucial for developing targeted interventions in teacher training programs, emphasizing emotional skills and self-belief as key drivers of effective teaching in early-childhood education.